(3QjGV GdCOHs - (3ejQRG LYaQ GdgePGfj, QjGVs ((3MSf GdMdHi s)
(3ChdgG (B:s
(3CeG HYO aEf ddCOH QjGVkG eeQYI hMjGVkG eJQYI hMOjbI GdaVd ZdH CTLGQgG , YPH CKeGQgG s
(3BNQgG (B:s
(3Ke EbJYOfG YjQGfg hegQjG hGJNPfG Gdbhe XgQjG s
(3cGf GdeDda MjC SfI (B1269 (3g`s
(3ebGeGJ COHjI aQY ef JCdjagG (B1269 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B152s
Keywords: (3GdCOHs